rozłóż na czynniki wielomiany
a) (x2 + 5)(x2 - 12x + 36)
b) x3 - 9x
c) x3 + 4x2 - 4x - 16
d) x6 + 2x5 + 2x4 + 4x3
a)
b)
c)
d)
(x²+5)(x²-12x+36)=(x²+5)(x-6)²
x³-9x=x(x²-9)=x(x+3)(x-3)
x³+4x²-4x-16=x²(x+4)-4(x+4)=(x²-4)(x+4)=(x+2)(x-2)(x+4)
x⁶+2x⁵+2x⁴+4x³=x³(x³+2x²+2x+4)=x³(x²(x+2)+2(x+2))=x³(x²+2)(x+2)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a)
b)
c)
d)
a)
(x²+5)(x²-12x+36)=(x²+5)(x-6)²
b)
x³-9x=x(x²-9)=x(x+3)(x-3)
c)
x³+4x²-4x-16=x²(x+4)-4(x+4)=(x²-4)(x+4)=(x+2)(x-2)(x+4)
d)
x⁶+2x⁵+2x⁴+4x³=x³(x³+2x²+2x+4)=x³(x²(x+2)+2(x+2))=x³(x²+2)(x+2)